Hydration Process, Composition and Microstructure of Slag-Cement Paste Blends Containing 0-70 % Slag at Different Curing Temperatures - Zhang, Gaozhan; Ding, Qingjun; Gong, Zicheng; Sun, Daosheng; Wang, Aiguo (Asian Journal of Chemistry, 2014)
The hydration process, composition and microstructure of slag-cement paste blends with 0-70 % slag at different curing temperatures have been studied by hydration heat test, XRD, high resolution solid-state 29Si MAS NMR and SEM. The results demonstrate that curing temperatures and dosage of slag are the key factors to influence hydration process, microstructure of slag-cement pastes during setting. With the curing temperatures increase, the exothermic peak shift forwards, the amount of calcium hydroxide (CH) decreased, the maximum hydration heat power, the microstructure parameters of calcium silicate hydrate (C-S-H): Q2/Q1 ratios, Al/Si ratios, the mean aluminosilicate chain length (MCL) for C-S-H, the hydration rate of cement (ac), the hydration rate of slag (as) and the degree of polymerization of C-S-H increase and the morphology of C-S-H gradually tends to be more bulky and dense. Similarly, with the dosage of slag in the blends increase, the exothermic peak shift afterwards, the maximum hydration heat power and the amount of calcium hydroxide decrease, the microstructure parameters of C-S-H: Q2/Q1 ratios, Al/Si ratios and MCL, ac, the degree of polymerization of C-S-H increase and the morphology of C-S-H gradually changes from needle and flocculate to graininess.